Health Perspectives of Thai Muslim on Tuberculosis - Lillahkul, Niratchara; Noin, Jetsadakorn; Noradechannunt, Chaiya (Princess of Naradhiwas University Journal, 2021)
The objective of this phenomenal qualitative study was to explain the views of Thai Muslims on tuberculosis. The informants were 10 patients diagnosed with tuberculosis. Qualitative data were collected by interviewing and non-participatory observation. The data were analyzed using the Van Manen’s analysis. Results showed that the patients had the viewpoints towards tuberculosis into 3 types which were: 1) a disease caused by the will of God; 2) a lung disease; and 3) a disease that must be concealed and not be disclosed. As for the effects of tuberculosis with on Tuberculosis’ drug, it could be divided into 4 characteristics which were: 1) exhaustion or fatigue; 2) numbness liked a needle pierced; 3) lack of income or reduced income; and 4) depletion of religious practice. The results indicated that tuberculosis-infected patients suffered from physical, mental, economic, and social illness. When taking tuberculosis drugs, adverse reactions from the use of drugs led to increased suffering. Incorrect and improper management could result in the lack of continuity of medication and the spread of infection in families and communities. Therefore, in the care of these patients, the healthcare team should have understanding on the context of faith and beliefs of Thai Muslim clients. They should also have the ability to provide appropriate self-care and prevention of infectious spread under the context of faith, beliefs and cultures. This would help encourage the patients to take care of themselves, as well as to manage the adverse symptoms caused by tuberculosis medication and reduce the suffering from their illness.